Passive Design Strategy in Vernacular House of Samin, Indonesia - Agung Murti Nugroho (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2024)
Vernacular architecture embodies passive design principles and strategies to create comfortable dwellings. This study investigates the impact of passive design strategies on temperature comfort in Samin vernacular houses. Visual observation is employed to assess the suitability of house elements based on passive design criteria. At the same time, field measurements are conducted to evaluate comfortable temperature conditions using data loggers over one month. The research focuses on the Original Samin house and the New Samin house situated in Klopoduwur Village, Blora Regency, Central Java, Indonesia. The visual observation reveals that the roof volume, slope, and thin walls with low conductivity in both Samin houses align with passive design principles. The New Samin house also incorporates other passive design strategies, including an east-west building orientation with the long side perpendicular to the wind direction, an open-plan room layout, and varying floor heights. The temperature comfort performance in both houses falls within the neutral temperature range during 16 hours. The New Samin house exhibits the largest daytime air temperature decrease at 5.5°C, while the Original Samin house experiences the largest nighttime decrease at 0.7°C. The evolution of passive designs in Samin vernacular houses encompasses considerations such as building proportion and width, terrace width, positioning and size of window openings, vegetation, and shading elements.